2017
DOI: 10.1186/s12864-017-4040-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the vertically transmitted microsporidian Facilispora margolisi and the parasiticide emamectin benzoate on salmon lice (Lepeophtheirus salmonis)

Abstract: BackgroundMicrosporidia are highly specialized, parasitic fungi that infect a wide range of eukaryotic hosts from all major taxa. Infections cause a variety of damaging effects on host physiology from increased stress to death. The microsporidian Facilispora margolisi infects the Pacific salmon louse (Lepeophtheirus salmonis oncorhynchi), an economically and ecologically important ectoparasitic copepod that can impact wild and cultured salmonids.ResultsVertical transmission of F. margolisi was demonstrated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…In the analysis, we found the biological process Protein folding enriched across 14 interactomes (Figure 2A). This biological process has been identified already as enriched and crucial in several host–pathogen systems, including mouse– P. falciparum (18); human– M. tuberculosis (42); B. glabrata – S. mansoni (43); L. salmonis – F. margolisi (44), based on transcriptomics and proteomics data. The protein folding biological process appears to be a conserved natural response to the infection and is related to a response to stress.…”
Section: Resultsmentioning
confidence: 99%
“…In the analysis, we found the biological process Protein folding enriched across 14 interactomes (Figure 2A). This biological process has been identified already as enriched and crucial in several host–pathogen systems, including mouse– P. falciparum (18); human– M. tuberculosis (42); B. glabrata – S. mansoni (43); L. salmonis – F. margolisi (44), based on transcriptomics and proteomics data. The protein folding biological process appears to be a conserved natural response to the infection and is related to a response to stress.…”
Section: Resultsmentioning
confidence: 99%
“…Going one step further, Borchel et al (2018) noted that 2 of the HSPs expressed by L. salmonis salmonis copepodids in response to salinity stress were also induced following exposure to the anti-louse treatment hydrogen peroxide. Poley et al (2017) also showed that HSc70 and HSP60 were induced in L. salmonis oncorhynchi copepodids infected with the microsporidian Facilispora margolisi and exposed to the anti-louse treatment emamectin benzoate. Other known pathways for freshwater tolerance in crustaceans include reduced cuticular permeability, ability to excrete urine that is more dilute than hemolymph and adaptation to lower hemolymph osmolality relative to stenohaline species (Pequeux 1995).…”
Section: Mechanisms Of Freshwater Tolerancementioning
confidence: 87%
“…If the parasite traces the same route as the host's genetic information-is vertically transmitted-then co-structuring can be expected. Vertical transmission may occur transovarially, such as in many Microsporidia, for example Facilispora margolisi Jones et al parasitising the copepod Lepeophtheirus salmonis (Krøyer) [15]. Vertical transmission may also occur if the parasite from parent host taints the egg integument which is then ingested by the offspring [16].…”
Section: I) Mode Of Transmissionmentioning
confidence: 99%